Plastic In Skincare Cosmetics: An Investigation of the Acceptance of Plastic Packaging and Micro-Plastics When Buying Skincare Products - Mehn, Audrey; Vogt, Virginia Odessa Nisha (International Journal of Applied Research in Management and Economics, 2020)
Never before has so much plastic existed within the environment as is currently the case. Cosmetics are a significant part of the plastic problem, both in terms of microplastics in the ingredients and through plastic-containing packaging. Generation Y is often seen as being environmentally conscious and sustainable. Contrary to this, however, Generation Y has proven to be carefree when buying plastic cosmetics. This article is intended to clarify the question of why German women of Generation Y buy plastic-contaminated, caring facial cosmetics, even though they are aware of possible damage. Results of an online survey (N=337) and a qualitative survey with experts revealed that the leading causes for the purchase of plastic-containing, caring cosmetics include the lack of plastic-free alternative products, the lack of transparency of product declarations and the enormous amount of time involved in the search for plastic-free cosmetic.